Factors promoting informal and formal learning strategies among school leaders. Issue 2 (3rd May 2020) - Rodriguez-Gomez, David; Ion, Georgeta; Mercader, Cristina; López-Crespo, Saida
ABSTRACT: The professional development of principals is a key element in improving the quality of educational systems. Although it is common for the training of educational leaders to be associated to formal pre- and in-service principal development programmes, informal learning opportunities are increasingly common. However, research analysing informal learning processes among this professional group is scarce. The purpose of this paper is to identify the factors promoting informal learning strategies, online and face-to-face, used by principals as part of their professional development. The methodology involved implementing an online self-administered questionnaire to a sample of 715 school leaders. The study begins with a univariate and bivariate descriptive analysis. Three multiple regression models are then developed, which allow to check the independent effects among the variable criteria used and the three types of learning methods under consideration. The results show that the development of formal and informal learning activities among principals clearly requires a 'learning-friendly' organisational culture, a clear motivation for the profession, a strong professional determination and a positive perception of professional competencies as principals. Schools should start promoting the transition from job-based to competence-based staff systems and structures, in which informal learning strategies become relevant as a basis for promoting innovation.